Charging cables for electric vehicles of rated voltages up to and including 0, 6/1 kV. Cables for DC charging according to mode 4 of IEC 61851-1. Cables intended to be used with a thermal management system Part 4-2, (6th July 2021) - British Standards Institution,
No abstract available